ABADAM: un Modelo de Seguridad para el Acceso a Bases de Datos Utilizando Agentes Móviles - Franco Borré, David Antonio; Moya Villa, Yasmín; Quintana Álvarez, Moisés; García Bolaños, Miguel Angel; Rodríguez Ribón, Julio Cesar (Ingeniería, 2007)
This article analyze aspects related to the mobile agents and security problems these entail, presenting a model access to databases that allow in a high degree to improve the response times in the network and to create a security model that collaborates with user’s authentication process. The proposed model has denominated ABADAM (Access to Databases using Mobile Agents), ABADAM was implemented using: the Java programming language, API Aglets and MS-SQL Server. ABADAM offers a high level of security to protect the database server from malicious agents attacks, allowing access to the valid agents only. The security is based fundamentally on the authentication or identification process of agents that arrive to the server, this process will be able to detect non-valid agents and it will eliminate when considering them malicious agents. In addition if some ill-disposed user created a mobile agent with login and password valid will not be able to make the authentication when it will not be carrying the credential that credits it as a reliable agent and it would be destroyed immediately.